Identification of DNS covert channel based on improved convolutional neural network - Meng ZHANG; Haoliang SUN; Peng YANG (Tongxin xuebao)
In order to effectively identify the multiple types of DNS covert channels,the implementation of different sorts of DNS covert channel software was studied,and a detection based on the improved convolutional neural network was proposed.The experimental results,grounded upon the campus network traffic,show that the detection can identify twenty-two kinds of data interaction modes of DNS covert channels and is able to identify the unknown DNS covert channel traffic.The proposed method outperforms the existing methods.